2005
DOI: 10.1007/s11199-005-8307-1
|View full text |Cite
|
Sign up to set email alerts
|

Television Commercials as a Lagging Social Indicator: Gender Role Stereotypes in Korean Television Advertising

Abstract: Previous studies of mass media in many countries have confirmed that images of women are stereotypical and unrealistic, particularly in television advertising. This study was designed to analyze the representation of gender roles in Korean television advertising and to compare the results with previous studies conducted in other countries. A sample of 878 Korean television advertisements from the MBC network in 2001 was content analyzed. Findings indicate that women in Korean television advertising were portra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 37 publications
5
76
2
3
Order By: Relevance
“…Most studies in Hong Kong reported a predominance of male characters (Furnham & Chan, 2003;Furnham et al, 2000), while studies on South Korea showed a predominance of female characters (Kim & Lowry, 2005;Paek et al, 2011;Prieler, 2012). In contrast, Moon and Chan (2007) reported no statistically significant differences for both cultures.…”
Section: Literature Review Hypotheses and Research Questionmentioning
confidence: 87%
See 1 more Smart Citation
“…Most studies in Hong Kong reported a predominance of male characters (Furnham & Chan, 2003;Furnham et al, 2000), while studies on South Korea showed a predominance of female characters (Kim & Lowry, 2005;Paek et al, 2011;Prieler, 2012). In contrast, Moon and Chan (2007) reported no statistically significant differences for both cultures.…”
Section: Literature Review Hypotheses and Research Questionmentioning
confidence: 87%
“…English language studies on Asian countries began in the 1990s, including studies on Singapore (Lee, 2004;Siu & Au, 1997;Tan, Ling & Theng, 2002;Wee, Choong & Tambyah, 1995), Malaysia (Bresnahan et al, 2001;Tan et al, 2002;Wee et al, 1995), China (Cheng, 1997;Paek, Nelson & Vilela, 2011;Siu & Au, 1997), Indonesia (Furnham, Mak & Tanidjojo, 2000), and the Philippines (Prieler & Centeno, 2013). There have also been several studies on Hong Kong (Furnham & Chan, 2003;Furnham et al, 2000;Moon & Chan, 2007), Japan (Arima, 2003;Bresnahan et al, 2001;Furnham & Imadzu, 2002;Milner & Collins, 2000), and South Korea (Kim & Lowry, 2005;Moon & Chan, 2007;Paek et al, 2011;Prieler, 2012). However, there is no comparative study of all three cultures to date, which makes this multicultural study even more timely.…”
Section: Literature Review Hypotheses and Research Questionmentioning
confidence: 99%
“…Además de ser mucho menos común la presencia de mujeres que de hombres, se ha encontrado que es más probable que los personajes femeninos presentados en los medios sean más jóvenes que los masculinos (Furnham y Skae, 1997;Ganahl, Prensen y Netzley, 2003;Kim Lowry, 2005;Uray y Burnaz, 2003;Valls-Fernández y Martínez-Vicente, 2007); que se valore en mayor medida su apariencia física (Malkin, Wornian y Chrisles, 1999); y que se les trate con mayor frecuencia como objetos sexuales (Bogt, Engels, Bogers y Kloosterman, 2010;Coltrane y Adams, 1997;Millar y Grant, 2006;Wallis, 2011).…”
Section: Introductionunclassified
“…In the developed countries the stereotypes oriented to the discrimination seems to be decreasing (Kim & Lowry, 2005), but the analyse carried by Steinghen, Eisend and Knoll (2009) in a longitudinal analysis shows us that there is no change of the gender stereotyping in TV advertising over time.…”
Section: Gender Stereotyping In Advertisementmentioning
confidence: 97%